Desenvolver a cidadania através da química : é possível? Um desafio a ser vencido - Azevedo, Leonardo Ribeiro de (Universidade Federal de São Carlos, 2003)
The present work was inspired by the High School National Curriculum Parameters (PCNEM) as well the Schnetzler proposal of teaching chemistry to citizenship. It is also based on the observed chemistry teaching problems, inefficiency of teaching methodologies and governmental programs. Teaching chemistry under the viewpoint of maintainable social and environmental development offers opportunities to relate the work to the customary student daily life, the construction of concepts starting from facts, and of knowledge about information bound to the human being survival. The interpretation of these information was carried out using concepts already established and others concepts were built up to understand the subjects. This work applied a new methodological proposal (strategy) based on the constructive conceptions and the idea that chemistry should be taught to build up the basic abilities for citizenship, seeking to evaluate the teaching and learning process and also the method acceptance. The approach to the contents took in account the interdisciplinary, using Chemistry Science as a tool to interpret the facts in the real world. The results showed that the applied teaching methodology, according to PCNEM, was able to improve the student’s participation. The students started to act as managers of the learning process, being capable to supervise and elaborate their own ideas comparing them with the previously established scientific ideas. It was also observed that the scientific activity became something joyful and gratifying to the students.
Keywords: Cidadania; Ensino; Química; Cotidiano; Desafio; CIENCIAS EXATAS E DA TERRA::QUIMICA